Reinvestigating the Impact of Conference Realignment on Rivalry in Intercollegiate Athletics - Cody T. Havard; Daniel L. Wann; Timothy D. Ryan (Journal of Applied Sports Management, 2017)
The current study investigated the influence of a U.S. intercollegiate team competing in a new conference for multiple seasons on fan perceptions of rival teams and likelihood of considering anonymous aggression toward rival teams. Fans of teams that changed conferences during conference realignment reserved stronger negative perceptions of the former rival on factors involving on-field competition and stronger negative perceptions of the current rival on factors involving off-field competition. Additionally, fans were more likely to consider committing anonymous acts of aggression against the former rival team than the current rival team. Implications and directions for future study are discussed.
Keywords: Rivalry; fan rival perceptions; fan behavior; anonymous aggression; conference realignment